THE INFLUENCE OF PERCEIVED VALUE, CUSTOMER TRUST, AND PRICE ON SWITCHING INTENTION THROUGH CUSTOMER SATISFACTION IN ONLINE TRANSPORTATION SERVICES: A CASE STUDY OF MAXIM APPLICATION AMONG GENERATION Z IN PADANG CITY: PENGARUH PERCEIVED VALUE, CUSTOMER TRUST, DAN PRICE TERHADAP SWITCHING INTENTION MELALUI CUSTOMER SATISFACTION PADA JASA TRANSPORTASI ONLINE APLIKASI MAXIM DI KALANGAN GENERASI Z DI KOTA PADANG - Raisa Amina Ismet; Dina Patrisia (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
The increasing competition in the online transportation industry has led to a growing trend of switching intention among Generation Z users, particularly in urban areas like Padang. This study aims to analyze the influence of Perceived Value, Customer Trust, and Price on Switching Intention through Customer Satisfaction among Maxim application users. Using a quantitative research method, data were collected through a survey distributed to Generation Z respondents in Padang who actively use the Maxim application. The study employed Partial Least Squares – Structural Equation Modeling (PLS-SEM) for data analysis. The findings indicate that Perceived Value and Customer Trust positively influence Customer Satisfaction, which in turn reduces Switching Intention. Meanwhile, Price significantly affects Customer Satisfaction, but in some cases, a higher price may increase the likelihood of switching if not accompanied by quality service. Furthermore, Customer Satisfaction acts as a crucial mediating variable, strengthening or weakening the relationship between Perceived Value and Price with Switching Intention. These findings contribute to a better understanding of consumer behavior in the digital transportation sector, highlighting the importance of maintaining customer satisfaction to ensure long-term loyalty. Future research is encouraged to explore additional factors such as brand loyalty, user experience, and service differentiation strategies